Vitamin D in the complex treatment of diabetes type 2 patients - Yephimov, A. S.; Orlenko, V. L.; Mykhaltchuk, L.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The level of providing the bodies with vitamin D of diabetes type 2 patients is researched, and its total deficit at the given category of patients is established. The dependence of the compensation of diabetes type 2 on the level of the vitamin D deficit is revealed. The analysis of the provideness of a body with general vitamin D in the dependence on getting a sugar decreasing therapy is performed. The effectiveness of the correction of the vitamin D deficit state by the application of Alfacalcidol to the patients with various types of sugar decreasing therapy is shown. The positive influence of the medicine on the compensation of the main disease has been proved. The effectiveness of Alfacalcidol in the correction of osteopenia of the patients with diabetes arthropathy is demonstrated.